Analisis Logam Merkuri (Hg) pada Air Sungai Janja di Derah Pertambangan - Mita Rosita; Tri Santoso; Sitti Aminah; Sri Hastuti Virgianti Pulukadang (Media Eksakta, 2022)
Mercury metal (Hg) is included in the heavy metal group which is toxic because it has neurotoxin properties for living things. As a heavy metal, mercury (Hg) will be difficult to decompose if it enters the waters, mercury (Hg) will also form deposits in sediments. Mercury is found in nature and is found in soil, water and air. Mercury is rarely found in its free form in nature but is in the form of cinnabar (HgS) seeds. Mercury metal is usually easy to find in mining areas, such as in gold mining areas. Gold mining is one of the activities that can increase people's income, but gold mining can be detrimental if in its implementation it is not followed by a good gold processing waste treatment process. The method used in this research is cold vapor atomic absorption spectrophotometry. The results obtained in this study are the metal content of miner 1 as many as 3 samples. Sample 1 has a concentration of 1.2594 ppm; sample 2 has a concentration of 0.4924 ppm; and sample 3 has a concentration of 0.2091 ppm. Miner 2 as many as 3 samples of which sample 1 has a concentration of 1.0260 ppm; sample 2 has a concentration of 0.3401 ppm; and sample 3 has a concentration of 0.3152 ppm. And miner 3 has 3 samples where sample 1 has a concentration of 0.7215 ppm; sample 2 has a concentration of 0.2464 ppm; and sample 3 has a concentration of 0.3461 ppm. The results obtained from the calculation of metal concentrations of mercury (Hg) show that the water of the Janja river has been contaminated with heavy metals, namely mercury (Hg). This is due to mining in the Janja river.